Service substitution method based on composition context - Hai-yan WANG; Si-rui LI (Tongxin xuebao)
With the variety of requirements from service requesters and the increasing complexity of network environ-ments,service composition has become more and more complicated.In order to decrease redundant information of the substituted service and improve the accuracy of service substitution,the composition context was regarded as the match-ing criteria and tried to substitute failed service with the following two steps.First,a composition context information collecting algorithm (CCICA) was proposed based on the color petri net model of the service workflow,and regarded the composition context as the collecting source of service information.Second,a levenshtein distance-based service substi-tution method (LDBSSM) was given,which was integrated with dependencies between service interfaces.Simulation re-sults show that the proposed LDBSSM method is practical because it can not only reduce redundancy of substituted ser-vice information but also effectively improve the accuracy of service substitution.